A Universal Human Right to Shape Responses to a Global Problem? The Role of Self‐Determination in Guiding the International Legal Response to Climate Change. Issue 1 (April 2017) - Maguire, Amy; McGee, Jeffrey
Abstract : International climate change law is at a critical juncture. Two decades of international treaty negotiations have delivered rising greenhouse gas emissions and minimal adaptation funding. The pattern of negotiations suggests that key States will often only make significant commitments that are aligned with their material interests and reciprocated by their competitors. This 'logic of reciprocity' in international climate negotiations has limited ambition such that vulnerable States are facing existential threats from sea level rise, storm surge and salt‐water inundation. We consider whether the international legal system offers any alternative logics that might found a duty on emitters to reduce their emissions in a timelier fashion and respond to climate‐change‐induced forced migration. We therefore focus on the foundational principle of the self‐determination of peoples, a collective human right which has supported movements towards decolonization and the emancipation of oppressed peoples. We argue that self‐determination might offer an alternative logic of duty on high‐emitting States to the plight of populations who find their territory (and potentially their nationhood) under threat from anthropogenic climate change.